Fully right pure group rings - Alsarahead, Mikhled; Ahmad, Mohamed Kheir (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper, we study the pure right ideal in rings, and then the fully right pure rings. The necessary and sufficient conditions for a ring